n2=6n

Simple and best practice solution for n2=6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n2=6n equation:



n2=6n
We move all terms to the left:
n2-(6n)=0
We add all the numbers together, and all the variables
n^2-6n=0
a = 1; b = -6; c = 0;
Δ = b2-4ac
Δ = -62-4·1·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{36}=6$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-6}{2*1}=\frac{0}{2} =0 $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+6}{2*1}=\frac{12}{2} =6 $

See similar equations:

| 7t+7+9t-11=360 | | u/5​ −2=0 | | v.2=-6 | | u/5−2=0 | | 7t+7+9t-11=90 | | -4x-9=-5x+3 | | v2=-6 | | 34+(4x+8)=180 | | 5(x+1)+55=90 | | -4x-9=-5x=+3 | | 34+(4x-8)=280 | | –3x–4=23 | | f/3+5=41 | | 2x+4=2x+3x-10-10 | | -6(2x+6)=-7 | | 3(x+3)-5=-23 | | 2x+5x-4=7(x+1=-5 | | -33=-3(1-5a) | | -10x=4x-4 | | e5=18 | | 5(x+13)+5=20 | | 2+n3=5 | | k3-2=-2 | | x=4x-2+3x=3x+12+4x-14 | | (7x+104)=3 | | -6x+7(2x-7)=15 | | -4k-3=39 | | x=6x+5-2x=4+4x+1 | | 3y+8-9y=-70 | | x=13-(2x+2)=2(x+2)+3x | | 2^2x+4=256 | | 0.25q=2.75 |

Equations solver categories